Development of a technique for identification of model parameters of high-pressure discharge lamp - Якунін, Олексій Анатолійович (Eastern-European Journal of Enterprise Technologies, 2015)
The technique for identification (determination of the parameters) of the model of high-pressure discharge lamp by comparing the simulated and experimental data was developed. Searching for the model parameters is divided into two main stages: 1) determining the degree of influence of each parameter change on the model output; 2) directly searching for the minimum functional divergence. Divergence evaluation is carried out by determining the value of the functional - the sum of the squares of divergences during the studied time period. When searching for minimum divergence, a corresponding set of model parameters is determined. The technique for determining the parameters of the mathematical model of high-pressure discharge lamp was designed to determine such parameters of the model, which allow to describe it with the necessary precision. Trial computational experiment showed the performance of the model parameter determination program, developed using the technique. It was found that the models that are based on the current-voltage characteristics of lamps are promising. The need to determine the model parameters is caused by the requirement for the accuracy of the research, and the availability of regular deviations in characteristics of lamps of the same type from different manufacturers, batches and even between units in batches from that of manufacturers and general. Ensuring the model accuracy is also important in developing and creating complex control systems that can be realized with microprocessor control, where the model is used for calculating the control object behavior and selecting control signals.